Development of prismatic skylight roofing construction system for Malaysia Tropical buildings. - Abdul Rahman, Abdul Malek (Universiti Sains Malaysia, 2014)

(untitled)
Daylighting has been considered as a potential energy-efficient design strategy for buildings. The excessive and highly exposed to solar radiation on buildings in tropical region such us Malaysia during all year cause overheating problems. Most of the electricity consumed in Malaysian buildings is used for a thermally and visually comfortable built-environment through air-conditioning and artificial lighting.